Using the network of SIRGAS stations of Costa Rica for quantifying the discrepancies regarding PPP online processing - Moya Zamora, Jorge (2017)
Discrepancies in geocentric coordinates [X,Y,Z] obtained between GPS solutions processed online with the software of the Canadian Space Reference System (CSRS) in the form of Precise Point Positioning (PPP) and weekly solutions obtained were quantified by a scientific postprocessing generated by the geocentric system for the Americas (SIRGAS). The network has 10 stations SIRGAS-CON, network of Costa Rica, which used a year of daily data between weeks 1803 (July 2014) of and 1854 (July 2015). The implemented methodology processed 3614 online rinex files of 24 hours with the CSRS service. The results allowed to quantify the PPP discrepancies between the coordinates daily, average weekly discrepancies PPP solution and finally the average solution discrepancies regarding the final weekly SIRGAS solution. These discrepancies were used to make a national estimate by an interpolation with IDW method. The results of the PPP and SIRGAS solutions were used to determine the six transformation parameters for each week included in the study. The results were significant with values of -58.5 ± 17.5 mm, -34.3 mm ± 6.2 mm and 26.2 mm ± -161.6 mm for translations at [X,Y,Z] respectively and average rotations in the three axes of 0.003600” ± 0.000341”. These results showed a translation in the north-south direction of the PPP solution regarding SIRGAS. PPP results obtained were used to estimate the components of the geocentric speed of each station and are compared to the values given by SIRGAS.